Isorhamnetin Alleviates Airway Inflammation by Regulating the Nrf2/Keap1 Pathway in a Mouse Model of COPD - Xu, Yifan; Li, Jing; Lin, Zhiwei; Liang, Weiquan; Qin, Lijie; Ding, Jiabin; Chen, Shuqi; Zhou, Luqian (Frontiers in Pharmacology, 2022)
Chronic obstructive pulmonary disease (COPD) is a severely disabling chronic lung disease characterized by persistent airway inflammation, which leads to limited expiratory airflow that deteriorates over time. Isorhamnetin (Iso) is one of the most important active components in the fruit of Hippophae rhamnoides L. and leaves of Ginkgo biloba L, which is widely used in many pulmonary disease studies because of its anti-inflammatory effects. Here, we investigated the pharmacological action of Iso in CS-induced airway inflammation and dissected the anti-inflammation mechanisms of Iso in COPD mice. A mouse model of COPD was established by exposure to cigarette smoke (CS) and intratracheal inhalation of lipopolysaccharide (LPS). Our results illustrated that Iso treatment significantly reduced leukocyte recruitment and excessive secretion of interleukin-6 (IL-6), monocyte chemoattractant protein-1 (MCP-1), and regulated upon activation, normal T-cell expressed and secreted (RANTES) in BALF of CS-induced COPD mice in a dose-dependent manner. This improved airway collagen deposition and emphysema, and further alleviated the decline in lung functions and systemic symptoms of hypoxia and weight loss. Additionally, Iso treatment obviously improves the T lymphocyte dysregulationin peripheral blood of COPD mice. Mechanistically, Iso may degrade Keap1 through ubiquitination of p62, thereby activating the nuclear factor erythroid 2-related factor (Nrf2) pathway to increase the expression of protective factors, such as heme oxygenase-1 (HO-1), superoxide dismutase (SOD)1, and SOD2, in lungs of CS-exposed mice, which plays an anti-inflammatory role in COPD. In conclusion, our study indicates that Iso significantly alleviates the inflammatory response in CS-induced COPD mice mainly by affecting the Nrf2/Keap1 pathway. More importantly, Iso exhibited anti-inflammatory effects comparable with Dex in COPD and we did not observe discernible side effects of Iso. The high safety profile of Iso may make it a potential drug candidate for COPD.